Zwroty czasownikowo-rzeczownikowe o tematyce futbolowej w słowniku rosyjsko-polskim/polsko-rosyjskim - Fedorushkov, Yury (Studia Rossica Posnaniensia, 2018)
A football lexicon contains a lot of unregistered phrasemes. The text of the article is devoted to the input method of verbal-nominative phrases from the text corpora into the bilingual (Russian-Polish / Polish-Russian) pocket dictionary of soccer.